Design, modeling, and characterization of a pulsed cold spray system - Gabor, Ted; Wang, Yijie; Akin, Semih; Zhou, Fengfeng; Chen, Jun; Jeon, Yongho; Jun, Martin Byung Guk (Surface and Coatings Technology, 2025)
Pulsed cold spray (PCS) is a type of cold spray metal coating technique that incorporates cyclical compressed gas pulses to control the gas-powder for improved surface deposition. In recent years, PCS has garnered great attention owing to its unique pulsed nature in the domains of dense coatings, metal matrix composite coatings, cellular metallic structures, etc. However, research on the PCS to uncover process-structure-property relationships of this emerging deposition technique is limited. To this end, this study thoroughly investigates PCS to gain a deeper understanding of this coating technique. First, a PCS system incorporating a converging-diverging (CD) nozzle is designed and prototyped. Next, two-phase flow (i.e., gas + powder) within the PCS is modeled using computational fluid dynamics (CFD). The modeling results are then experimentally validated using particle image velocimetry (PIV), followed by a case study on surface deposition. The results show that the optimal powder injection window occurs when the gas inlet pressure is at least 99 % of the set inlet pressure, achieving a steady-state gas flow for 100 ms. CFD modeling showed that Mach diamonds formed at the nozzle exit by 30 ms, though powder velocity does not reach steady-state until 50 ms. Numerical modeling captured the average particle with an error of ≈8 % as compared to the PIV measurements. Furthermore, surface deposition experiments showed that the PCS can create dense coatings with remarkably less porosity (i.e., 1.73-fold) as compared to the traditional CS. Overall, this study unravels the intricacies of designing and modeling of a PCS system with a CD nozzle, complemented by surface deposition experiments.
Keywords: Cold spray; Computational fluid; Computational fluid dynamic; Fluid-dynamics; Image velocimetry; Particle image velocimetry; Particle images; Polymer metallization; Pulsed cold spray; Cold spray; Computational fluid dynamics (CFD); Numerical modeling; Particle image velocimetry (PIV); Polymer metallization; Pulsed cold spray